Dziga Vertov’s Cinema as a Language of Temporal Reflection - A. E. Yakimov (Дискурс)
Introduction. The article is devoted to the general theoretical analysis of Dziga Vertov’s cinema as a language of temporal reflection. According to essential hypothesis of this research Vertov’s work expresses the feature of the temporal regime of the culture of Soviet modernity.Methodology and sources. The author uses the terms “temporal reflection” and “time regime of culture” guided by the A. Assmann’s work “Is Time Out of Joint? On the Rise and Fall of the Modern Time Regime”. The article is rethinking these concepts and point out as a methodological ground for the analysis of non-fiction cinematography.Results and discussion. As a result of the analysis of both Vertov’s films and texts and theoretical works devoted to the study of his work, it is argued that Vertov’s non-fiction films could be considered as a symbolic language of temporal reflection. Particular attention is paid to Vertov’s both theoretical works and manifestos, and at the technical level – to the cinematographic techniques and means of expression of time. The temporal regime of modernity according to the Assmann includes features such as the turning point of time, the fiction of a new beginning, creative destruction, the emergence of the concept of “historical” and the acceleration of time. The analysis of the film “Man with a Movie Camera” (1929) given in the article demonstrates that Vertov’s work expresses these features. This conclusion is also confirmed by a number of theoretical positions in Vertov’s works, some of which are presented in the article.Conclusion. Based on the analysis, it is concluded that Vertov’s cinematic experiments are inventing a new language for comprehending time of history and culture. This language functions on account of the mechanical reduction of reality and the synthesis of the resulting images-perceptions based on the principle of ideological and poetic advisability.